2013
DOI: 10.1016/j.nlm.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms are responsible for dishabituation of electrophysiological auditory responses to a change in acoustic identity than to a change in stimulus location

Abstract: Repeated exposure to an auditory stimulus leads to habituation of the electrophysiological and immediate-early-gene (IEG) expression response in the auditory system. A novel auditory stimulus reinstates this response in a form of dishabituation. This has been interpreted as the start of new memory formation for this novel stimulus. Changes in the location of an otherwise identical auditory stimulus can also dishabituate the IEG expression response. This has been interpreted as an integration of stimulus identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…Our results show the repetition-induced decrease in responses, described by numerous studies both in mammals (Malmierca et al, 2014;Khouri and Nelken, 2015) and songbirds (Chew et al, 1995;Stripling et al, 1997;Phan et al, 2006;Beckers and Gahr, 2012;Smulders and Jarvis, 2013;Lu and Vicario, 2014). Once neuronal responses were decreased, the presentation of a novel song, generally sung by a distinct individual, resets the responses Figure 10.…”
Section: Sensitivity To the Temporal Order Of Syllables In Conspecifisupporting
confidence: 61%
“…Our results show the repetition-induced decrease in responses, described by numerous studies both in mammals (Malmierca et al, 2014;Khouri and Nelken, 2015) and songbirds (Chew et al, 1995;Stripling et al, 1997;Phan et al, 2006;Beckers and Gahr, 2012;Smulders and Jarvis, 2013;Lu and Vicario, 2014). Once neuronal responses were decreased, the presentation of a novel song, generally sung by a distinct individual, resets the responses Figure 10.…”
Section: Sensitivity To the Temporal Order Of Syllables In Conspecifisupporting
confidence: 61%
“…Our results in adult animals build on a well-established paradigm in which recent auditory experience is encoded in adult and developing NCM (Chew et al, 1995;Stripling et al, 1997;Smulders and Jarvis, 2013;Miller-Sims and Bottjer, 2014;Ono et al, 2016). As in prior reports, we observed robust auditory recognition memory in the NCM of adults, regardless of treatment group.…”
Section: Recent Auditory Experience Consolidation Is Insensitive To Esupporting
confidence: 86%
“…Boynton, ; Van Ruijssevelt et al , ). Regarding real‐time in situ neuronal responses, for example, studies using electrophysiology have recorded conspecific‐selective firing patterns from individual neurons at the microsecond scale (Chew et al , ; Chew, Vicario, & Nottebohm, ; Woolley, Hauber, & Theunissen, ; Hauber et al , ; Smulders & Jarvis, ). Brain imaging, such as functional magnetic resonance imaging (fMRI) and positron emission tomography (PET), also showed that conspecific sounds evoke greater neural activity at a stimulus‐length (several seconds) time scale, when compared to sequential playbacks of heterospecific sounds (Poirier et al , ; Louder et al , ; Lattin, Stabile, & Carson, ).…”
Section: Neural Responses To Species‐specific Soundsmentioning
confidence: 99%
“…Several different techniques have demonstrated the role of the avian auditory forebrain in differential processing of acoustic stimuli from different species, even when presenting sounds produced by unfamiliar individuals. Studies using electrophysiology have recorded conspecific‐selective greater firing for neurons within Field L (Woolley et al , ; Hauber et al , ), as well as in the NCM and CMM (Chew et al , , ; Smulders & Jarvis, ). fMRI and PET showed that conspecific sounds evoke greater neural activity when compared to heterospecific sounds (Poirier et al , ; Louder et al , ; Lattin et al , ).…”
Section: Neural Regions Involved In Species‐specific Discriminationmentioning
confidence: 99%
See 1 more Smart Citation